ANALISIS KITAB AL MUSTASHFA KARYA AL GHAZALI - Sholikhul Hadi (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
end of the second and third centuries, Imam Muhammad binIdris Asy-syafi'i (150-204 H) founder of the Shafi'i school,appeared in concocting, systematizing and recording the usul fiqh.He was the first to record the science of ushul fiqh with his bookentitled Al-Risalah. The ushul fiqh analysts say that during thefourth time the imam of the school, ushul fiqh finds its perfect form,so that later generations tend to choose and use the methodaccording to the case faced in their own time. In particular thebook of Al Mustashfa is interesting to peel, because the book iscomposed not only by using Shafi'iyyah method but also otherapproaches such as philosophy and tasawuf.